Analysis of shrinkage stresses arising during polymerization of orthodontic adhesive systems - Konrad Malkiewicz; Michał Krasowski; Jakub Bartczak; Marta Radziejewska; Kinga Bociong (Polimery)
The aim of the study was to evaluate the shrinkage stress during cross-linking of composite orthodontic adhesive systems. The elastic-optical method was used for shrinkage stress analysis. Based on the obtained results, basic statistics were determined, including averages and standard deviations. For the comparative analysis of the mean values, the Tukey HSD test was used at the significance level α = 0.05. The average value of shrinkage stress during cross-linking ranged from 7.2 to 11.5 MPa.